Production and Performance Evaluation of Noble Fire Extinguishing Foam Suspensions Using Locally Available and Environmentally Friendly Natural Mineral Raw Materials - Gurchumelia, Lali; Tsarakhov, Murman; Tkemaladze, Salome; Bejanov, Feliks; Tkemaladze, Lasha (Chemical Engineering Research Bulletin, 2020)
The main goal of this research is the fabrication of halogen free, environmentally friendly fire-extinguishing powders using local mineral raw materials and the development of technological processes for producing highly efficient fire-extinguishing foam-suspensions on the basis of the produced powders. Fire-extinguishing powders are made by mechanical treatment and mixing of raw materials: zeolite, clay shale, perlite and ammophos. The process does not need introduction of expensive, halogen-containing, hydrophobizators and ensures the cost-effective production of fire-extinguishing powders. The obtained fire-extinguishing powders are characterized by high performance properties, high fire-extinguishing capacity and coefficient of atomic oxygen recombination. Thus, they are characterized both by homogeneous and heterogeneous inhibition of combustion processes. The efficiency of the produced powders is not inferior to that of standard powders of common production. In addition, in contrast to their traditional analogs they are halogen free, environmentally friendly and cheaper (1.2-2 times cheaper). The obtained powders, unlike the ones of conventional production, have good compatibility with water and foam. Our foam-suspensions are prepared just by mechanical mixing of fire-extinguishing powders with water and surface-active substances – foamers. The process does not require chemical treatment of materials. Thus, the developed technology is simple and cost-effective. The foam-suspensions produced on the basis of the obtained powders have higher heat capacity, permeability, wetting effect like water and foam and unlike them, they allow for homogeneous as well as heterogeneous inhibition of the burning process. Thus, the so produced foam-suspensions will have higher extinguishing effect than water, foams or powders, taken separately. Based on the above, it can be suggested that the produced powders can be used for extinguishing all types of fires, including large-scale ones in a combination with water and foams. Chemical Engineering Research Bulletin 21(2019) 58-64